Damage to the public health system caused by war-related looting or vandalism in the Tigray region of Northern Ethiopia - Gufue, Zenawi Hagos; Haftu, Hiluf Kalayou; Alemayehu, Yibrah; Tsegay, Etsay Weldekidan; Mengesha, Meresa Berwo; Dessalegn, Berhe (Frontiers in Public Health, 2024)
Background: The war that started on November 4, 2020, in the Tigray region of northern Ethiopia severely affected the health sector. However, there is no available evidence to suggest the economic damage caused to the public health system because of war-related looting or vandalism. This study was aimed at estimating the cost of war-related looting or vandalism in Tigray's public health system in northern Ethiopia in 2021. Methods: A provider perspective, a mixed costing method, a retrospective cross-sectional approach, a 50% inflation rate, and a 50 Ethiopian birr equivalent to one United States dollar () for the money value were used. The data were analyzed using Microsoft Excel, taking into consideration the Sendai framework indicators. Results: The total economic cost of the war-related looting or vandalism in monetary terms was more than 3.78 billion, and the damage to the economic value in monetary terms was more than 2.31 billion. Meanwhile, the direct economic loss to the health system in monetary terms was more than 511 million. According to this assessment, 514 (80.6%) health posts, 153 (73.6%) health centers, 16 (80%) primary hospitals, 10 (83.3%) general hospitals, and 2 (100%) specialized hospitals were damaged and/or vandalized either fully or partially due to the war. Conclusions: This war seriously affected the public health sector in the Tigray region. The Federal Government of Ethiopia, the Ministry of Health of Ethiopia, the Tigrayan Government, the Tigray Regional Health Bureau, and the international community must make efforts to find resources for the revitalization of the damaged, plundered, and vandalized healthcare system.